2023
DOI: 10.1186/s13619-023-00175-6
|View full text |Cite|
|
Sign up to set email alerts
|

Generating hematopoietic cells from human pluripotent stem cells: approaches, progress and challenges

Haiqiong Zheng,
Yijin Chen,
Qian Luo
et al.

Abstract: Human pluripotent stem cells (hPSCs) have been suggested as a potential source for the production of blood cells for clinical application. In two decades, almost all types of blood cells can be successfully generated from hPSCs through various differentiated strategies. Meanwhile, with a deeper understanding of hematopoiesis, higher efficiency of generating progenitors and precursors of blood cells from hPSCs is achieved. However, how to generate large-scale mature functional cells from hPSCs for clinical use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 203 publications
0
2
0
Order By: Relevance
“…For example, hematopoietic lineage cells can be derived by sequential specification of the mesoderm and the hemogenic endothelium to obtain hematopoietic progenitor cells followed by terminal differentiation of lymphoid and myeloid lineages in the presence of relevant cytokines. 150,151 Neural cells can be derived by dual SMAD inhibition that promotes neuroectoderm specification and the emergence of neural progenitor cells (Fig. 2a).…”
Section: Ipsc-derived Cellular Modelsmentioning
confidence: 99%
“…For example, hematopoietic lineage cells can be derived by sequential specification of the mesoderm and the hemogenic endothelium to obtain hematopoietic progenitor cells followed by terminal differentiation of lymphoid and myeloid lineages in the presence of relevant cytokines. 150,151 Neural cells can be derived by dual SMAD inhibition that promotes neuroectoderm specification and the emergence of neural progenitor cells (Fig. 2a).…”
Section: Ipsc-derived Cellular Modelsmentioning
confidence: 99%
“…Following publication of the original article (Zheng et al 2023 ), the authors reported that Figs. 1 and 2 were in the wrong order.…”
mentioning
confidence: 99%